Bryoflora Salvadorensis 3. An updated checklist and new records of Pottiaceae for El Salvador - Búcaro, Rosa Delia; Sollman, Philip; Stech, Michael (Phytotaxa, 2019)
An updated list of the taxa of the moss family Pottiaceae recorded for El Salvador is presented, based on literature reports and own investigations. At present, 20 genera of Pottiaceae are known from El Salvador, of which four (Barbula, Scopelophila, Trichostomum, Weissia) are reported as new for the country. Eight species and two varieties are reported as new for El Salvador: Barbula orizabensis, Bryoerythrophyllum ferruginascens, B. inaequalifolium, Chionoloma tenuirostre, Didymodon acutus var. icmadophilus, Hyophila nymaniana, Leptodontium viticulosoides var. viticulosoides, Scopelophila cataractae, Trichostomum brachydontium, and Weissia jamaicensis, increasing the total number of species to 35. Information on the distribution, main substrate types, and approximate elevational range in Mesoamerica as well as the general distribution are provided for all taxa.